High Prevalence of Cefiderocol Resistance Among New Delhi Metallo-β-Lactamase Producing Klebsiella pneumoniae High-Risk Clones in Hungary - Lilla Buzgó; Zsanett Kiss; Dániel Göbhardter; Virág Lesinszki; Erika Ungvári; Zoltán Rádai; Levente Laczkó; Ivelina Damjanova; Gábor Kardos; Ákos Tóth (Antibiotics)
Background/Objectives: The global spread of carbapenemase-producing K. pneumoniae (CPKP) strains represent a severe public health threat due to very limited choice of antibacterial therapy. Cefiderocol, a novel siderophore-cephalosporin, may represent a new therapeutic option but resistance is increasingly being described. Our aim was to investigate in vitro cefiderocol susceptibility among CPKP strains in Hungary and assess correlations between resistance, carbapenemase types, and clonal lineages. Methods: The study was performed on 420 CPKP strains from 34 Hungarian healthcare institutes (HCIs) submitted to the National Reference Laboratory of Antimicrobial Resistance (March 2021 to April 2023). The disk diffusion method (Liofilchem, Via Scozia, Italy) was used for in vitro cefiderocol susceptibility testing (according to EUCAST guidelines). For molecular epidemiologic investigation, we used whole genome sequencing (Illumina MiSeq, 150 bp paired-end) and pulsed-field gel electrophoresis (PFGE). Carbapenemase gene type was determined by multiplex PCR. Statistical analysis was performed in R (v.4.2.0). Results: Dominant high-risk clones (ST147, ST395, ST258) exhibited regional distribution, with ST147/NDM-1 strains showing the highest cefiderocol resistance (75%). Overall resistance was 65%. Carbapenemase gene types occurred as follows: 35 blaVIM, 53 blaKPC, 57 blaOXA-48-like, 153 blaNDM, and 122 blaOXA-48-like+blaNDM. Cefiderocol resistance rates by carbapenemase type were 20%, 44%, 70%, and 75% in the case of blaVIM, blaOXA-48-like, blaKPC, blaNDM, and blaOXA-48-like+blaNDM. Conclusions: The results show a high prevalence of cefiderocol resistance in CPKP in Hungary, with different rates of resistance in different carbapenemase gene-carrying high-risk clones, highlighting the growing challenge in treating these infections.